Pengembangan Dokumentasi Keperawatan Berbasis Elektronik Di RS X Kota Depok Dengan Menggunakan Teori Perubahan Lewins - Dyah Fitri Wulandari; Hanny Handiyani ((JKG) Jurnal Keperawatan Global, 2019)
Background: Nursing documentation in Indonesia is still much in the form of paper based documentation. Many weaknesses in this documentation model, so it needs to be innovated by using electronic-based nursing documentation. Problems that occur in RS X in the development of electronic-based nursing documentation are the factors of leadership, factors of means and factors of follow-up development of electronic nursing documentation. Method: In solving this problem, it is recommended to use Lewin's theory of change which consists of three phases: unfreezing, moving, and refreezing. Result: Stages of unfreezing: conducting evidence-based and literature review studies on the importance of electronic documentation, and brainstorming with the nurse actors change Phase Moving implementing the stages of implementation of electronic documentation development using the principles of 5 management functions namely planning, organizing, staffing, leading and controlling. Refreezing stages: provide supervisors, make Decree of Director and Standard of Operational Procedure about implementation of electronic-based nursing documentationin X Hospital Depok. Conclusion: In solving this problem, Lewin's theory of change consists of three pairs, namely unfreezing, moving, and refreezing.